2000
DOI: 10.1074/jbc.275.19.14231
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42-induced Activation of the Mixed-Lineage Kinase SPRKin Vivo

Abstract: Src homology 3 domain (SH3)-containing proline-rich protein kinase (SPRK)/mixed-lineage kinase (MLK)-3 is a serine/threonine kinase that upon overexpression in mammalian cells activates the c-Jun NH 2 -terminal kinase pathway. The mechanisms by which SPRK activity is regulated are not well understood. The small Rho family GTPases, Rac and Cdc42, have been shown to bind and modulate the activities of signaling proteins, including SPRK, which contain Cdc42/Rac interactive binding motifs. Coexpression of SPRK and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 59 publications
3
44
0
Order By: Relevance
“…MLK3 has also been shown to activate the MAPK p38 kinase pathway via MKK3/6 (Tibbles et al, 1996) and the extracellular signal-related protein kinase (ERK) pathway (Hartkamp et al, 1999). In addition, expression of a dominant negative mutant of MLK3 led to a reduction in the Cdc42-dependent activation of JNK (Teramoto et al, 1996), and MLK3 CRIB domain has been shown to be required for its association with and activation by Cdc42 in human embryonic kidney 293 cells (Bock et al, 2000). Altogether, these studies strongly suggest that MLK3 may be an important element within the mechanism of stress-induced activation of the JNK pathway and of neuronal death.…”
Section: Abstract: Apoptosis; Cdc42; Mlk3; Signal Transduction; Sympsupporting
confidence: 50%
“…MLK3 has also been shown to activate the MAPK p38 kinase pathway via MKK3/6 (Tibbles et al, 1996) and the extracellular signal-related protein kinase (ERK) pathway (Hartkamp et al, 1999). In addition, expression of a dominant negative mutant of MLK3 led to a reduction in the Cdc42-dependent activation of JNK (Teramoto et al, 1996), and MLK3 CRIB domain has been shown to be required for its association with and activation by Cdc42 in human embryonic kidney 293 cells (Bock et al, 2000). Altogether, these studies strongly suggest that MLK3 may be an important element within the mechanism of stress-induced activation of the JNK pathway and of neuronal death.…”
Section: Abstract: Apoptosis; Cdc42; Mlk3; Signal Transduction; Sympsupporting
confidence: 50%
“…Known activators of mixed-lineage kinases include members of the small Rho-family GTPases (34,(38)(39)(40). Among these GTPase molecules are the Rac, Rho, and cdc42 proteins.…”
Section: Dal-1 Activation Of Jnk Is Dependent On Rac1 Activationmentioning
confidence: 99%
“…The small GTPase Cdc42, in its activated state, binds to MLK3 through the centrally located CRIB motif, and increases MLK3 catalytic activity (5)(6)(7). This activation is accompanied by a change in the phosphopeptide map pattern of in vivo labeled MLK3, suggesting that Cdc42 binding induces activating phosphorylation event(s) on MLK3 (7). A leucine zipper that resides NH 2 -terminal to the CRIB motif is necessary for MLK3 homo-oligomerization (8).…”
mentioning
confidence: 99%